ROAD THICKNESS ANALYSIS USING MDP METHOD 2017 (CASE: PURWODADI – NONGKOJAJAR) - Ratna Handayani; Ahmad Faathir Wicaksono (Journal Innovation of Civil Engineering (JICE), 2021)
The Purwodadi - Nongkojajar road section is one of the East Java Province roads in UPT PJJ Probolinggo, which received funding from the Regional Road Grant Program (PHJD). From the results of the road condition survey in 2020, the condition of road damage in the form of holes and hair cracks was obtained. Based on this, it was necessary planning the thickness of the re-pavement or overlay. This program begins with inventory and road condition, topographic and soil investigation surveys. From the results of the topographic survey, we can measure the slope, then we conduct an investigative survey using Benkelman-beam deflection measure tool to determine the back- deflection value. References and secondary data of traffic growth and road class data are collected. The thickness of the pavement was calculated using the MDP 2017 method. This research found that the required layer was AC-WC layer with an expected thickness of 4 cm. Due to the uneven condition of the existing road, an additional leveling layer AC-BC was needed to overcome this condition with a thickness of 3.0 cm.